Combine effect of soft drink tins and polypropylene fibres on mechanical properties of concrete - Syamsir A.; Adnan W.; Anggraini V.; Zahari N.M.; Norhisham S.; Beddu S.; Itam Z. (American Institute of Physics Inc., 2023)
The combine effect of soft drink tins (SDT) and polypropylene (PP) fiber on mechanical properties of concrete such as compressive and flexural strengths were observed in this research. In this research it is found that by combining 0.2% of SDT with 0.2 % PP fiber has increase compressive strength of concrete by 30% and 18.4 % for SDT 30mm and 60mm long, respectively. It was also observed by using the same combination for SDT 60mm has increase flexural strength of concrete by 23.8% and 12.6 % for SDT 30mm and 60mm long, respectively. It is concluded that the optimum fiber contents are 0.2% for SDT and PP and the use of 30mm long SDT fiber has better performance as compared to 60mm SDT fibre. 2020 Author(s).